Academic Misconduct Responsibilities: An Empirical Comparison Using 35 Chinese Cases as a Foundation - Cao, Wenze; Cao, Zhaoxun; Rajamanickam, Ramalinggam; Dahlan, Nur Khalidah (Hasanuddin Law Review, 2025)
This article undertakes a comprehensive exploration of academic misconduct by employing a robust comparative and empirical approach. It meticulously examines 35 representative cases from China, delving into the diverse manifestations of academic misconduct such as fund project evaluation interference, fraud, paper trading, improper authorship, and multiple submissions. Through in-depth legal analysis, it not only investigates the infringements on intellectual property rights and public legal interests but also proposes the application of strict liability in tort law. To enhance the regulatory framework, the article advocates for clearer criminalization criteria for severe academic misconduct. It further extends the discussion to incorporate the roles of academic institutions, the challenges in enforcement, and a more expansive legal framework. By drawing on international experiences and best practices, it formulates comprehensive and actionable suggestions for reforming China's academic misconduct regulations, aiming to address this issue effectively on both national and international levels.